Managing the flow of goods and services within globalized environments - Dr. Tarun Lata (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The challenges related to sustainability in the production, distribution, and consumption of goods and services are increasingly putting pressure on the credibility of corporations. Existing literature identifies three common strategies employed by corporations to address issues of legitimacy: conforming to external expectations, shaping stakeholder perceptions, or engaging in a dialogue with those questioning their legitimacy. This discussion explores three methods for determining the most suitable response strategy: the one-best-way approach, contingency approach, and paradox approach. The argument presented suggests that, when confronted with diverse environments and conflicting demands, corporations adopting a paradoxical approach are more likely to successfully maintain their legitimacy compared to those choosing one of the other two approaches. A theoretical framework is developed to apply these response strategies, and the management of paradoxes is explored through structural, contextual, or reflective means.